Impact of internal auditing function on good corporate governance in Zimbabwe''s public sector ( 2012 -2016) - Zhanje, Kudzaishe Miranda (Midlands State University, 2020)
This paper examines the impact of internal audit function on good corporate governance in the public sector in Zimbabwe with particular attention on the State Owned Enterprises (SOEs). The focus was on the effect of internal audit on the risk management, internal control, reporting and compliance to corporate governance. A survey of 140 respondents in the SOEs sector was carried out using the quantitative research h design anchored on the post positivism research philosophy using questionnaires. Data was collected and collated using the Likert scale. This study found out that internal auditing helps to ensure improved risk management processes, improves internal control system and also improves corporate reporting. Internal auditing as a pillar on the corporate governance process was also found to have a positive correlationship with corporate governance compliance in the SOEs sector in Zimbabwe. Implications of this study are that there is need for SOEs to improve the internal audit function through continuous development of the staff and adequately staffing the unit in order to ensure improved risk management functionalities, internal controls and corporate reporting.